Musicality and Intrafamily Translation: With Reference to European Languages and Chinese - Wong, Laurence (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractMost practitioners of translation agree that translation is at best an ersatz, able to get across only part of the source text’s meaning, which is meaning on two levels: the semantic and the phonological. Even in translating an apparently simple lexical item, to say nothing of long stretches of discourse, they are keenly aware of what is being left out. On the semantic level, for example, the denotation of a lexical item may sometimes be preserved almost intact. However, its connotations, associations, or nuances, which can elicit subtle responses from readers of the original, often defy the process of carrying over or across, which is what transferre, the Latin word from which translate is derived, means. Yet, compared with musicality, a feature on the phonological level, all features on the semantic level will become relatively easy. With reference to translations of Dante’s Divine Comedy in Spanish, French, Latin, English, German, and Chinese, as well as translations of Shakespeare’s Macbeth in Italian, this paper discusses musicality as the most recalcitrant of all features in a source-language text, and attempts to show how, depending on factors to be examined in detail, intrafamily translation, that is, translation between languages of the same family, can capture the original music with varying degrees of success.